Type 8 long QT syndrome: pathogenic variants in CACNA1C-encoded Cav1.2 cluster in STAC protein binding site. Issue 11 (13th August 2019) - Mellor, Greg J; Panwar, Pankaj; Lee, Andrea K; Steinberg, Christian; Hathaway, Julie A; Bartels, Kirsten; Christian, Susan; Balaji, Seshadri; Roberts, Jason D; Simpson, Chris S; Boczek, Nicole J; Tester, David J; et al.
Abstract: Aims: Pathogenic gain-of-function variants in CACAN1C cause type-8 long QT syndrome (LQT8). We sought to describe the electrocardiographic features in LQT8 and utilize molecular modelling to gain mechanistic insights into its genetic culprits. Methods and results: Rare variants in CACNA1C were identified from genetic testing laboratories. Treating physicians provided clinical information. Variant pathogenicity was independently assessed according to recent guidelines. Pathogenic (P) and likely pathogenic (LP) variants were mapped onto a 3D modelled structure of the Cav 1.2 protein. Nine P/LP variants, identified in 23 patients from 19 families with non-syndromic LQTS were identified. Six variants, found in 79% of families, clustered to a 4-residue section in the cytosolic II–III loop region which forms a region capable of binding STAC SH3 domains. Therefore, variants may affect binding of SH3-domain containing proteins. Arrhythmic events occurred in similar proportions of patients with II–III loop variants and with other P/LP variants (53% vs. 48%, P = 0.41) despite shorter QTc intervals (477 ± 31 ms vs. 515 ± 37 ms, P = 0.03). A history of sudden death was reported only in families with II–III loop variants (60% vs. 0%, P = 0.03). The predominant T-wave morphology was a late peaking T wave with a steep descending limb. Exercise testing demonstrated QTc prolongation on standing and at 4 min recovery after exercise. Conclusion: The majority of P/LP variants in patients with CACNA1C -mediated LQT8 cluster in an SH3-binding domain of the cytosolic II–III loop. This represents a 'mutation hotspot' in LQT8. A late-peaking T wave with a steep descending limb and QT prolongation on exercise are commonly seen.